2023
DOI: 10.1002/pits.22985
|View full text |Cite
|
Sign up to set email alerts
|

The effects of x‐axis time compression on the visual analysis of single‐case data

Abstract: Single‐case design is a research methodology that entails repeated measurement to assess the influence of an independent variable on a dependent variable over time. Data collected in this manner are regularly analyzed using visual analysis of data displayed in a linear graph. Although there is agreement regarding critical elements of visual analysis, research has highlighted poor reliability between raters. One potential contributor to this poor reliability are variations in visual presentation of the data dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Characteristics of the graphical displays of time-series data can meaningfully affect individuals’ interpretation of the data themselves (Dart & Radley, 2023; Radley et al, 2018). However, few studies on this topic have been conducted with practicing school psychologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the graphical displays of time-series data can meaningfully affect individuals’ interpretation of the data themselves (Dart & Radley, 2023; Radley et al, 2018). However, few studies on this topic have been conducted with practicing school psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies conducted by Radley, Dart, and colleagues provided strong evidence that aspects of the graphs in which SCD data are presented can influence raters’ decision making. For example, variations in the scaling of the Y -axis (Dart & Radley, 2017), the scaling of the X -axis (Dart & Radley, 2023), and the number of data points per X - to Y -axis ratio (DPPXYR; Radley et al, 2018), all influenced visual analysts’ identification of treatment effects and ratings regarding the magnitude of treatment effects. In fact, the manner in which graphs were assembled (e.g., Y -axis range, DPPXYR) had an impact on visual analysts’ judgements of the magnitude of effects even when the graphs were accompanied by a disclaimer that identified that graph manipulation was used to magnify intervention effects (Radley & Dart, 2023).…”
Section: Uses Of Time-series Graphs To Support Decisions In Mtssmentioning
confidence: 99%
“…The findings of Dart and Radley (2017), Radley et al (2018), and Dart and Radley (2023) provide initial evidence for two analysis-altering elements of graphs (Dart & Radley, 2018)—or graph construction features that influence visual analyst decisions. Subsequently, the identification of these elements may be used to inform the development of empirically derived guidelines for the graphic presentation of SCD data.…”
mentioning
confidence: 94%
“…Data were consistently rated by visual analysts as displaying a greater intervention effect when plotted on a graph with lower DPPXYR values than those with higher DPPXYR values. Dart and Radley (2023) subsequently found DPPXYR manipulation by way of x -axis time compression, or plotting data either by session (all data points plotted consecutively despite temporal gaps in data collection) or by calendar date (data plotted to represent temporal gaps in data collection), to impact visual analyst decisions. Findings indicated that when data were presented as session data (i.e., graphs with a lower DPPXYR value due to no visual gaps in data collection), visual analysts reported larger effects; when those same data were plotted by calendar date (i.e., graphs with a higher DPPXYR value due to gaps in data collection being accurately represented), visual analysts reported smaller intervention effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation